Efektivitas Tata Kelola Obyek Wisata Hutan Mangrove dalam Meningkatkan Perekonomian Masyarakat Desa Apar Kota Pariaman - Tiawarman, Hendri; Mubarak, Adil (PUBLICNESS: Journal of Public Administration Studies, 2023)
This study aims to determine the effectiveness of the management of mangrove forest tourism objects in improving the economy of the people of Apar Village, Pariaman City. The background of this research is the management of mangrove forest tourism objects by BUMDes which is not yet optimal and the level of welfare of the people of Apar Village who have not benefited from the existence of mangrove forest tourism objects. Researchers used a qualitative approach with descriptive qualitative methods. This study uses informant selection techniques using purposive sampling technique. The results of this study indicate that the effectiveness of managing mangrove forest tourism objects in improving the economy of the people of Apar Village, has not been effective. This is because there are still aspects of effectiveness and aspects of economic improvement that have not been fulfilled in the management of mangrove forest tourism objects, namely clarity of goals to be achieved, clarity of strategy for achieving goals, availability of facilities and infrastructure, implementation of effective and efficient tasks that have not been fulfilled. effectively or optimally. Furthermore, based on the economic improvement component, it has not been effective either. This is based on the aspect of increasing regional income, the aspect of increasing the average income of the community and the aspect of increasing the welfare of the community. As well as in the aspect of reducing unemployment rates it is also not very effective because there are still few job opportunities available in mangrove forest tourism objects.